Digital Transformation and Employee Performance: The Mediating Role of Self Efficacy in Commercial Banks of Butwal Sub-Metropolitan City - Bhusal, Shrinkhala (Journal of Economics and Management, 2026)
The research question to be discussed in this study is how the dimensions of digital transformation, including adoption of new technology, digital culture, digital leadership, and digital training programs, can impact on employee performance in commercial banks in Butwal, Nepal. Besides, the research also examines how self-efficacy mediates the interplay between digital transformation factors and employee performance. The study used descriptive and causal design research. A purposive sampling technique was used to sample 258 employees who were employed in commercial banks in Butwal. The responses were collected by a structured questionnaire comprising of a seven-point Likert scale (1 = strongly disagree to 7 = strongly agree). Partial Least Squares Structural Equation Modeling (PLS-SEM) was used in the data analysis. Outer loadings, Variance Inflation Factor (VIF), composite reliability, and Heterotrait Monomethod (HTMT) ratio were used to test the measurement model. Mean and standard deviation were calculated to give a summary of the responses. The hypothesized relationships and mediation effects were tested using bootstrapping procedures. The findings suggest that digital leadership positively influences the performance of employees the most with digital training programs coming second. The beta coefficients of both variables are relatively large compared to the rest of the digital transformation factors. Moreover, self-efficacy also plays a significant role in mediating digital culture, adoption of new technology, digital training programs, and performance of employees. This implies that the positivity of digital transformation initiatives on performance outcomes is increased by the fact that the employees have confidence in their digital skills. The results emphasize the importance of digital leadership and guided digital training courses in enhancing the performance of employees. The management of the bank needs to focus and work on development of leaders in the competencies of digital offerings and should invest in ongoing digital skills improvement programs. The effectiveness of the digital transformation in the banking field can be also maximized by reinforcing the self-efficacy of employees, which can be achieved through supportive leadership and target training.